Livelihood Strategy of Poor Female-Headed Households in Basic Household Expenses - Mujahiddin Mujahiddin; Ananda Mahardika (Budapest International Research and Critics University, 2019)
Based on data released by Empowerment of female heads of household. it is known that one-sixth of households in Indonesia are led by women and 60 percent of these women live in very poor conditions. It is not easy for every individual or family who lives in a state of poverty to be able to meet the basic needs of his family. In this study several concepts and theoretical descriptions are explained which concern the understanding of female heads of household, poverty and basic household expenses. The research method used a qualitative approach with the study of five poor female heads of household who were in Paya Geli Village, Sunggal District, Deli Serdang District, North Sumatra. The data collection techniques using in-depth interviews with data analysis techniques using a qualitative approach to interactive models as proposed by Miles and Huberman which consists of three main things, namely: Data reduction, data presentation, and conclusion / verification. The results of the study show that the livelihood strategies undertaken by female heads of poor households in their basic families needs are by reducing family food consumption, debt to neighbors or relatives and asking for helping from children who have worked. This strategy is carried out because the income generated by the family head or family member has not been fully capable of fulfill basic household expenses